Towards the construction of a mechanism supported in fuzzy logic to evaluate the viability of businesses under the canvas model - Laura Daniela Acosta Contreras; Andrés Ricardo Barreto López; Carlos Enrique Montenegro Marín; Paulo Alonso Gaona García (Revista Escuela de Administracion de Negocios, 2018)
This article aims at showing the first functional approximation to the creation of a mechanism which generates a viability indicator of of a producto r a business plan base don the design of Canvas Model as well as using Emis Benchmarking Score as a referential issue suggested by Euromoney Institutional Inversor Company (EMIS), an organization which reveals company financial information. This approximation focuses on the application of fuzzy logic as a tool for analyzing and generating this indicator. Based on the data and information generated by a fuzzy stated system and experimental figures, a Pearson correlation coefficient was used to measure this behavioral model, resulting in 88 % which